Endoscopic Findings of Gastro-Esophageal Reflux Disease in Elderly and Younger Age Groups - Adanir, Haydar; Baş, Bilge; Pakoz, Betul; Günay, Süleyman; Camyar, Hakan; Ustaoglu, Muge (Frontiers in Medicine, 2021)
Objective: To determine and compare the clinical features and endoscopic findings of gastro-esophageal reflux disease (GERD) in elderly and younger age groups. Materials and Methods: The clinical and endoscopic features were evaluated for all patients with GERD between January 2017 and September 2020. The criteria for inclusion were being aged over 65 and under 50 years and having an upper gastrointestinal endoscopy with reflux symptoms resistant to ppi theraphy. The exclusion criteria included prior surgery, age under 18 years, and pregnancy. The diagnosis of GERD was made according to the patients' symptoms. The SPSS 11.0 for Windows pocket program was used for statistical analysis. Results: Two hundred eighty-six patients aged over 65 years and 261 patients aged below 50 years were enrolled in this study. The mean age of the older group was 68.2 ± 4.5 years and the mean age of the young group was 38 ± 7.2 years. The male/female ratio was 5/3 and 2/1 in the young and older groups, respectively. The older patients had less severe and rare typical symptoms than the young patients. However, significantly more serious endoscopic findings were noted in the older patients compared with the younger patients. Conclusion: The older and young patients with GERD were predominantly male and typical reflux problems were less common in older patients with GERD. Older patients had more important endoscopic findings such as hernia, esophagitis, and cancer.